Answer:
1/6
Step-by-step explanation:
gradient= change in y/ change in x
-4--5/2--4= 1/6
1/6 is the gradient
Answer:
(-2,1)
Step-by-step explanation:
hi
f°g mean apply g(x) and then use result of g(x) as "x" in f(x)
so as g(x) = x² +1 and f(x) = 3x+2
so if we call g(x) X we have
f( X) = 3 X +2
now we replace " X" for it's value
f(X) = 3 ( x² +1) +2
f(X) = 3x² +3 +2
f(X) = 3x² +5
so f°g = 3x² +5
Answer:Looking at myy profile u know im dumb
Step-by-step explanation:
31/2+3/4+3/4+4/4 or 1
7/2+3/4+3/4+4/4
14/4+3/4+3/4+4/4 =24/4=6
Ans = 6 cups